Exploring redox behavior of mixed manganese‒cobalt spinel oxides through in situ analysis - Adjah‐Tetteh, Christabel; Smith, Kayla S.; He, Zizhou; Wang, Yudong; Xu, Nengneng; Zhou, Xiao‐Dong (Journal of the American Ceramic Society, 2025)
Investigating the redox behavior of manganese‒cobalt spinel oxides is essential for optimizing their electrical, catalytic, and electrochemical properties that depend on the oxidation states of Mn and Co ions. In this work, we investigated a series of Mn x Co 3‒ x O 4 (MCO, x  = 0‒3) through in situ thermogravimetric and structural analysis to evaluate how the MCO composition affects structure, phase evolution, and redox transition temperatures. Reduction in MCO proceeds via two steps whereas reoxidation of the reduction products (MnO and Co) commonly occurs in a single step. Manganese is seen to reduce the reoxidation temperatures ‐ the spinel peak was first evident at 300°C for x = 2.4 whereas that of x = 0.6 appeared at 400°C . Cobalt‐ and manganese‐rich contents ( x  = 0.6 and 2.4) gave rise to CoO and Mn 2 O 3 secondary phases respectively during reoxidation. These secondary phases were first observed when the temperature reached 500°C, however, such phases diminished with increasing temperature, yielding a single phase at 800°C. In contrast, the mid‐range composition ( x  = 1.8) yields single spinel phases at relatively lower temperatures. We also studied the relationship between composition and morphology of exsolved Co and MnO particles during reduction, which are of importance to catalytic applications. These findings can offer guidelines for designing MCO for catalytic and electrochemical applications.